Importance of Housing and Cardiovascular Health and Well-Being: A Scientific Statement From the American Heart Association. Issue 8 (August 2020) - Sims, Mario; Kershaw, Kiarri N.; Breathett, Khadijah; Jackson, Elizabeth A.; Lewis, Lisa M.; Mujahid, Mahasin S.; Suglia, Shakira F.
Abstract : Cardiovascular disease disparities are shaped by differences in risk factors across racial and ethnic groups. Housing remains an important social determinant of health. The objective of this statement is to review and summarize research that has examined the associations of housing status with cardiovascular health and overall health. PubMed/Medline, Centers for Disease Control and Prevention data, US Census data, Cochrane Library reviews, and the annual Heart Disease and Stroke Statistics report from the American Heart Association were used to identify empirical research studies that examined associations of housing with cardiovascular health and overall well-being. Health is affected by 4 prominent dimensions of housing: stability, quality and safety, affordability and accessibility, and neighborhood environment. Vulnerable and underserved populations are adversely affected by housing insecurity and homelessness, are at risk for lower-quality and unsafe housing conditions, confront structural barriers that limit access to affordable housing, and are at risk for living in areas with substandard built environment features that are linked to cardiovascular disease. Research linking select pathways to cardiovascular health is relatively strong, but research gaps in other housing pathways and cardiovascular health remain. Efforts to eliminate cardiovascular disease disparities have recently emphasized the importance of social determinants of health. Housing is a prominent social determinant of cardiovascular health and well-being and should be considered in the evaluation of prevention efforts to reduce and eliminate racial/ethnic and socioeconomic disparities.